Conjunctions in English scientific articles: an analysis on conjunctive adjuncts linking sentences - Taufan, Gullit Tornado; Wicaksono, Julien Arief (Politeknik Negeri Jember, 2020)
This study focuses on the use of conjunctive adjuncts that link one sentence to another in 20 English scientific articles published in four different journals. Text analysis is employed to investigate the use of conjunctive expressions, the most frequently used categories and forms of conjunctive adjuncts, and possible patterns in the use of conjunctions based on Halliday and Hasan’s (1976) framework. 221 items of conjunctive expressions are found covering 24.69% of the total number of sentences written. Additive conjunction is the category which is the most frequently used, while ‘however’ is the form which is used in the highest frequency. Unfortunately, this study is quite far from sufficient to draw a conclusion regarding the possible patterns of the use of the conjunctions in the subject journals.